Large reduction in the magnitude and thermal variation of Frank elastic constants in a gold nanorod/nematic composite - Madhuri, P. Lakshmi; Prasad, S. Krishna; Shinde, Pravin; Bhagavatula L. V. Prasad (Journal of Physics D: Applied Physics, 2016)
We report measurements of splay and bend Frank elastic constants in a composite comprising a nematic liquid crystal doped with a small concentration of sterically stabilized gold nanorods. The composite exhibits not only a large reduction in the magnitude of the threshold voltage for switching (Vth, 20%), as well as of the splay (K11, 40%) and bend (K33, 40%) elastic constants, but also presents an unprecedented feature: a substantial diminution in the temperature dependence of these parameters, almost to the point of becoming thermally invariant. This observation is significant because the electro-optic switching of liquid-crystal devices is largely controlled by the K11 and K33 elastic constants. Electrical conductivity measurements also show interesting behavior upon the inclusion of nanorods. Whereas the intrinsic Arrhenius behavior governing the temperature dependence is enhanced, the frequency dependence shows qualitative features of Jonscher’s universal model, albeit with a higher exponent. Further, photoisomerization of an azobenzene guest component provides an additional influence on the elastic constants. The results are discussed in terms of (a) the effect of the order parameter dependence seen from the viewpoint of an extended mean-field model,and (b) local order. The advantage of incorporating nanorods with photofunctionality is also pointed out.